lean2/library/algebra/group.lean

712 lines
22 KiB
Text

/-
Copyright (c) 2014 Jeremy Avigad. All rights reserved.
Released under Apache 2.0 license as described in the file LICENSE.
Authors: Jeremy Avigad, Leonardo de Moura
Various multiplicative and additive structures. Partially modeled on Isabelle's library.
-/
import logic.eq data.unit data.sigma data.prod
import algebra.binary algebra.priority
open binary
variable {A : Type}
/- semigroup -/
attribute inv [light 3]
attribute neg [light 3]
structure semigroup [class] (A : Type) extends has_mul A :=
(mul_assoc : ∀a b c, mul (mul a b) c = mul a (mul b c))
-- We add pattern hints to the following lemma because we want it to be used in both directions
-- at inst_simp strategy.
theorem mul.assoc [simp] [semigroup A] (a b c : A) : (: a * b * c :) = (: a * (b * c) :) :=
!semigroup.mul_assoc
structure comm_semigroup [class] (A : Type) extends semigroup A :=
(mul_comm : ∀a b, mul a b = mul b a)
theorem mul.comm [simp] [comm_semigroup A] (a b : A) : a * b = b * a :=
!comm_semigroup.mul_comm
theorem mul.left_comm [simp] [comm_semigroup A] (a b c : A) : a * (b * c) = b * (a * c) :=
binary.left_comm (@mul.comm A _) (@mul.assoc A _) a b c
theorem mul.right_comm [comm_semigroup A] (a b c : A) : (a * b) * c = (a * c) * b :=
by simp
structure left_cancel_semigroup [class] (A : Type) extends semigroup A :=
(mul_left_cancel : ∀a b c, mul a b = mul a c → b = c)
theorem mul.left_cancel [left_cancel_semigroup A] {a b c : A} : a * b = a * c → b = c :=
!left_cancel_semigroup.mul_left_cancel
abbreviation eq_of_mul_eq_mul_left' := @mul.left_cancel
structure right_cancel_semigroup [class] (A : Type) extends semigroup A :=
(mul_right_cancel : ∀a b c, mul a b = mul c b → a = c)
theorem mul.right_cancel [right_cancel_semigroup A] {a b c : A} : a * b = c * b → a = c :=
!right_cancel_semigroup.mul_right_cancel
abbreviation eq_of_mul_eq_mul_right' := @mul.right_cancel
/- additive semigroup -/
structure add_semigroup [class] (A : Type) extends has_add A :=
(add_assoc : ∀a b c, add (add a b) c = add a (add b c))
theorem add.assoc [simp] [add_semigroup A] (a b c : A) : (: a + b + c :) = (: a + (b + c) :) :=
!add_semigroup.add_assoc
structure add_comm_semigroup [class] (A : Type) extends add_semigroup A :=
(add_comm : ∀a b, add a b = add b a)
theorem add.comm [simp] [add_comm_semigroup A] (a b : A) : a + b = b + a :=
!add_comm_semigroup.add_comm
theorem add.left_comm [simp] [add_comm_semigroup A] (a b c : A) : a + (b + c) = b + (a + c) :=
binary.left_comm (@add.comm A _) (@add.assoc A _) a b c
theorem add.right_comm [add_comm_semigroup A] (a b c : A) : (a + b) + c = (a + c) + b :=
by simp
structure add_left_cancel_semigroup [class] (A : Type) extends add_semigroup A :=
(add_left_cancel : ∀a b c, add a b = add a c → b = c)
theorem add.left_cancel [add_left_cancel_semigroup A] {a b c : A} : a + b = a + c → b = c :=
!add_left_cancel_semigroup.add_left_cancel
abbreviation eq_of_add_eq_add_left := @add.left_cancel
structure add_right_cancel_semigroup [class] (A : Type) extends add_semigroup A :=
(add_right_cancel : ∀a b c, add a b = add c b → a = c)
theorem add.right_cancel [add_right_cancel_semigroup A] {a b c : A} : a + b = c + b → a = c :=
!add_right_cancel_semigroup.add_right_cancel
abbreviation eq_of_add_eq_add_right := @add.right_cancel
/- monoid -/
structure monoid [class] (A : Type) extends semigroup A, has_one A :=
(one_mul : ∀a, mul one a = a) (mul_one : ∀a, mul a one = a)
theorem one_mul [simp] [monoid A] (a : A) : 1 * a = a := !monoid.one_mul
theorem mul_one [simp] [monoid A] (a : A) : a * 1 = a := !monoid.mul_one
structure comm_monoid [class] (A : Type) extends monoid A, comm_semigroup A
/- additive monoid -/
structure add_monoid [class] (A : Type) extends add_semigroup A, has_zero A :=
(zero_add : ∀a, add zero a = a) (add_zero : ∀a, add a zero = a)
theorem zero_add [simp] [add_monoid A] (a : A) : 0 + a = a := !add_monoid.zero_add
theorem add_zero [simp] [add_monoid A] (a : A) : a + 0 = a := !add_monoid.add_zero
structure add_comm_monoid [class] (A : Type) extends add_monoid A, add_comm_semigroup A
definition add_monoid.to_monoid {A : Type} [add_monoid A] : monoid A :=
⦃ monoid,
mul := add_monoid.add,
mul_assoc := add_monoid.add_assoc,
one := add_monoid.zero A,
mul_one := add_monoid.add_zero,
one_mul := add_monoid.zero_add
definition add_comm_monoid.to_comm_monoid {A : Type} [add_comm_monoid A] : comm_monoid A :=
⦃ comm_monoid,
add_monoid.to_monoid,
mul_comm := add_comm_monoid.add_comm
section add_comm_monoid
variables [add_comm_monoid A]
theorem add_comm_three (a b c : A) : a + b + c = c + b + a :=
by simp
theorem add.comm4 : ∀ (n m k l : A), n + m + (k + l) = n + k + (m + l) :=
by simp
end add_comm_monoid
/- group -/
structure group [class] (A : Type) extends monoid A, has_inv A :=
(mul_left_inv : ∀a, mul (inv a) a = one)
-- Note: with more work, we could derive the axiom one_mul
section group
variable [group A]
theorem mul.left_inv [simp] (a : A) : a⁻¹ * a = 1 := !group.mul_left_inv
theorem inv_mul_cancel_left [simp] (a b : A) : a⁻¹ * (a * b) = b :=
by rewrite [-mul.assoc, mul.left_inv, one_mul]
theorem inv_mul_cancel_right [simp] (a b : A) : a * b⁻¹ * b = a :=
by simp
theorem inv_eq_of_mul_eq_one {a b : A} (H : a * b = 1) : a⁻¹ = b :=
have a⁻¹ * 1 = b, by inst_simp,
by inst_simp
theorem one_inv [simp] : 1⁻¹ = (1 : A) :=
inv_eq_of_mul_eq_one (one_mul 1)
theorem inv_inv [simp] (a : A) : (a⁻¹)⁻¹ = a :=
inv_eq_of_mul_eq_one (mul.left_inv a)
variable (A)
theorem left_inverse_inv : function.left_inverse (λ a : A, a⁻¹) (λ a, a⁻¹) :=
take a, inv_inv a
variable {A}
theorem inv.inj {a b : A} (H : a⁻¹ = b⁻¹) : a = b :=
have a = a⁻¹⁻¹, by simp_nohyps,
by inst_simp
theorem inv_eq_inv_iff_eq (a b : A) : a⁻¹ = b⁻¹ ↔ a = b :=
iff.intro (assume H, inv.inj H) (by simp)
theorem inv_eq_one_iff_eq_one (a : A) : a⁻¹ = 1 ↔ a = 1 :=
have a⁻¹ = 1⁻¹ ↔ a = 1, from inv_eq_inv_iff_eq a 1,
by simp
theorem eq_one_of_inv_eq_one (a : A) : a⁻¹ = 1 → a = 1 :=
iff.mp !inv_eq_one_iff_eq_one
theorem eq_inv_of_eq_inv {a b : A} (H : a = b⁻¹) : b = a⁻¹ :=
by simp
theorem eq_inv_iff_eq_inv (a b : A) : a = b⁻¹ ↔ b = a⁻¹ :=
iff.intro !eq_inv_of_eq_inv !eq_inv_of_eq_inv
theorem eq_inv_of_mul_eq_one {a b : A} (H : a * b = 1) : a = b⁻¹ :=
have a⁻¹ = b, from inv_eq_of_mul_eq_one H,
by inst_simp
theorem mul.right_inv [simp] (a : A) : a * a⁻¹ = 1 :=
have a = a⁻¹⁻¹, by simp,
by inst_simp
theorem mul_inv_cancel_left [simp] (a b : A) : a * (a⁻¹ * b) = b :=
by inst_simp
theorem mul_inv_cancel_right [simp] (a b : A) : a * b * b⁻¹ = a :=
by inst_simp
theorem mul_inv [simp] (a b : A) : (a * b)⁻¹ = b⁻¹ * a⁻¹ :=
inv_eq_of_mul_eq_one (by inst_simp)
theorem eq_of_mul_inv_eq_one {a b : A} (H : a * b⁻¹ = 1) : a = b :=
have a⁻¹ * 1 = a⁻¹, by inst_simp,
by inst_simp
theorem eq_mul_inv_of_mul_eq {a b c : A} (H : a * c = b) : a = b * c⁻¹ :=
by simp
theorem eq_inv_mul_of_mul_eq {a b c : A} (H : b * a = c) : a = b⁻¹ * c :=
by simp
theorem inv_mul_eq_of_eq_mul {a b c : A} (H : b = a * c) : a⁻¹ * b = c :=
by simp
theorem mul_inv_eq_of_eq_mul {a b c : A} (H : a = c * b) : a * b⁻¹ = c :=
by simp
theorem eq_mul_of_mul_inv_eq {a b c : A} (H : a * c⁻¹ = b) : a = b * c :=
by simp
theorem eq_mul_of_inv_mul_eq {a b c : A} (H : b⁻¹ * a = c) : a = b * c :=
by simp
theorem mul_eq_of_eq_inv_mul {a b c : A} (H : b = a⁻¹ * c) : a * b = c :=
by simp
theorem mul_eq_of_eq_mul_inv {a b c : A} (H : a = c * b⁻¹) : a * b = c :=
by simp
theorem mul_eq_iff_eq_inv_mul (a b c : A) : a * b = c ↔ b = a⁻¹ * c :=
iff.intro eq_inv_mul_of_mul_eq mul_eq_of_eq_inv_mul
theorem mul_eq_iff_eq_mul_inv (a b c : A) : a * b = c ↔ a = c * b⁻¹ :=
iff.intro eq_mul_inv_of_mul_eq mul_eq_of_eq_mul_inv
theorem mul_left_cancel {a b c : A} (H : a * b = a * c) : b = c :=
have a⁻¹ * (a * b) = b, by inst_simp,
by inst_simp
theorem mul_right_cancel {a b c : A} (H : a * b = c * b) : a = c :=
have a * b * b⁻¹ = a, by inst_simp,
by inst_simp
theorem mul_eq_one_of_mul_eq_one {a b : A} (H : b * a = 1) : a * b = 1 :=
by rewrite [-inv_eq_of_mul_eq_one H, mul.left_inv]
theorem mul_eq_one_iff_mul_eq_one (a b : A) : a * b = 1 ↔ b * a = 1 :=
iff.intro !mul_eq_one_of_mul_eq_one !mul_eq_one_of_mul_eq_one
definition conj_by (g a : A) := g * a * g⁻¹
definition is_conjugate (a b : A) := ∃ x, conj_by x b = a
local infixl ` ~ ` := is_conjugate
local infixr ` ∘c `:55 := conj_by
local attribute conj_by [reducible]
lemma conj_compose [simp] (f g a : A) : f ∘c g ∘c a = f*g ∘c a :=
by inst_simp
lemma conj_id [simp] (a : A) : 1 ∘c a = a :=
by inst_simp
lemma conj_one [simp] (g : A) : g ∘c 1 = 1 :=
by inst_simp
lemma conj_inv_cancel [simp] (g : A) : ∀ a, g⁻¹ ∘c g ∘c a = a :=
by inst_simp
lemma conj_inv [simp] (g : A) : ∀ a, (g ∘c a)⁻¹ = g ∘c a⁻¹ :=
by inst_simp
lemma is_conj.refl (a : A) : a ~ a := exists.intro 1 (conj_id a)
lemma is_conj.symm (a b : A) : a ~ b → b ~ a :=
assume Pab, obtain x (Pconj : x ∘c b = a), from Pab,
have Pxinv : x⁻¹ ∘c x ∘c b = x⁻¹ ∘c a, by simp,
exists.intro x⁻¹ (by simp)
lemma is_conj.trans (a b c : A) : a ~ b → b ~ c → a ~ c :=
assume Pab, assume Pbc,
obtain x (Px : x ∘c b = a), from Pab,
obtain y (Py : y ∘c c = b), from Pbc,
exists.intro (x*y) (by inst_simp)
end group
definition group.to_left_cancel_semigroup [trans_instance] [s : group A] :
left_cancel_semigroup A :=
⦃ left_cancel_semigroup, s,
mul_left_cancel := @mul_left_cancel A s ⦄
definition group.to_right_cancel_semigroup [trans_instance] [s : group A] :
right_cancel_semigroup A :=
⦃ right_cancel_semigroup, s,
mul_right_cancel := @mul_right_cancel A s ⦄
structure comm_group [class] (A : Type) extends group A, comm_monoid A
/- additive group -/
structure add_group [class] (A : Type) extends add_monoid A, has_neg A :=
(add_left_inv : ∀a, add (neg a) a = zero)
definition add_group.to_group {A : Type} [add_group A] : group A :=
⦃ group, add_monoid.to_monoid,
mul_left_inv := add_group.add_left_inv ⦄
section add_group
variables [s : add_group A]
include s
theorem add.left_inv [simp] (a : A) : -a + a = 0 := !add_group.add_left_inv
theorem neg_add_cancel_left [simp] (a b : A) : -a + (a + b) = b :=
calc -a + (a + b) = (-a + a) + b : by rewrite add.assoc
... = b : by simp
theorem neg_add_cancel_right [simp] (a b : A) : a + -b + b = a :=
by simp
theorem neg_eq_of_add_eq_zero {a b : A} (H : a + b = 0) : -a = b :=
have -a + 0 = b, by inst_simp,
by inst_simp
theorem neg_zero [simp] : -0 = (0 : A) := neg_eq_of_add_eq_zero (zero_add 0)
theorem neg_neg [simp] (a : A) : -(-a) = a := neg_eq_of_add_eq_zero (add.left_inv a)
variable (A)
theorem left_inverse_neg : function.left_inverse (λ a : A, - a) (λ a, - a) :=
take a, neg_neg a
variable {A}
theorem eq_neg_of_add_eq_zero {a b : A} (H : a + b = 0) : a = -b :=
have -a = b, from neg_eq_of_add_eq_zero H,
by inst_simp
theorem neg.inj {a b : A} (H : -a = -b) : a = b :=
have a = -(-a), by simp_nohyps,
by inst_simp
theorem neg_eq_neg_iff_eq (a b : A) : -a = -b ↔ a = b :=
iff.intro (assume H, neg.inj H) (by simp)
theorem eq_of_neg_eq_neg {a b : A} : -a = -b → a = b :=
iff.mp !neg_eq_neg_iff_eq
theorem neg_eq_zero_iff_eq_zero (a : A) : -a = 0 ↔ a = 0 :=
have -a = -0 ↔ a = 0, from neg_eq_neg_iff_eq a 0,
by simp
theorem eq_zero_of_neg_eq_zero {a : A} : -a = 0 → a = 0 :=
iff.mp !neg_eq_zero_iff_eq_zero
theorem eq_neg_of_eq_neg {a b : A} (H : a = -b) : b = -a :=
by simp
theorem eq_neg_iff_eq_neg (a b : A) : a = -b ↔ b = -a :=
iff.intro !eq_neg_of_eq_neg !eq_neg_of_eq_neg
theorem add.right_inv [simp] (a : A) : a + -a = 0 :=
have a = -(-a), by simp,
by inst_simp
theorem add_neg_cancel_left [simp] (a b : A) : a + (-a + b) = b :=
by inst_simp
theorem add_neg_cancel_right [simp] (a b : A) : a + b + -b = a :=
by simp
theorem neg_add_rev [simp] (a b : A) : -(a + b) = -b + -a :=
neg_eq_of_add_eq_zero (by simp)
-- TODO: delete these in favor of sub rules?
theorem eq_add_neg_of_add_eq {a b c : A} (H : a + c = b) : a = b + -c :=
by simp
theorem eq_neg_add_of_add_eq {a b c : A} (H : b + a = c) : a = -b + c :=
by simp
theorem neg_add_eq_of_eq_add {a b c : A} (H : b = a + c) : -a + b = c :=
by simp
theorem add_neg_eq_of_eq_add {a b c : A} (H : a = c + b) : a + -b = c :=
by simp
theorem eq_add_of_add_neg_eq {a b c : A} (H : a + -c = b) : a = b + c :=
by simp
theorem eq_add_of_neg_add_eq {a b c : A} (H : -b + a = c) : a = b + c :=
by simp
theorem add_eq_of_eq_neg_add {a b c : A} (H : b = -a + c) : a + b = c :=
by simp
theorem add_eq_of_eq_add_neg {a b c : A} (H : a = c + -b) : a + b = c :=
by simp
theorem add_eq_iff_eq_neg_add (a b c : A) : a + b = c ↔ b = -a + c :=
iff.intro eq_neg_add_of_add_eq add_eq_of_eq_neg_add
theorem add_eq_iff_eq_add_neg (a b c : A) : a + b = c ↔ a = c + -b :=
iff.intro eq_add_neg_of_add_eq add_eq_of_eq_add_neg
theorem add_left_cancel {a b c : A} (H : a + b = a + c) : b = c :=
have -a + (a + b) = b, by inst_simp,
by inst_simp
theorem add_right_cancel {a b c : A} (H : a + b = c + b) : a = c :=
have a + b + -b = a, by inst_simp,
by inst_simp
definition add_group.to_left_cancel_semigroup [trans_instance] : add_left_cancel_semigroup A :=
⦃ add_left_cancel_semigroup, s,
add_left_cancel := @add_left_cancel A s ⦄
definition add_group.to_add_right_cancel_semigroup [trans_instance] :
add_right_cancel_semigroup A :=
⦃ add_right_cancel_semigroup, s,
add_right_cancel := @add_right_cancel A s ⦄
theorem add_neg_eq_neg_add_rev {a b : A} : a + -b = -(b + -a) :=
by simp
theorem ne_add_of_ne_zero_right (a : A) {b : A} (H : b ≠ 0) : a ≠ b + a :=
begin
intro Heq,
apply H,
rewrite [-zero_add a at Heq{1}],
let Heq' := eq_of_add_eq_add_right Heq,
apply eq.symm Heq'
end
theorem ne_add_of_ne_zero_left (a : A) {b : A} (H : b ≠ 0) : a ≠ a + b :=
begin
intro Heq,
apply H,
rewrite [-add_zero a at Heq{1}],
let Heq' := eq_of_add_eq_add_left Heq,
apply eq.symm Heq'
end
/- sub -/
-- TODO: derive corresponding facts for div in a field
protected definition algebra.sub [reducible] (a b : A) : A := a + -b
definition add_group_has_sub [instance] : has_sub A :=
has_sub.mk algebra.sub
theorem sub_eq_add_neg [simp] (a b : A) : a - b = a + -b := rfl
theorem sub_self (a : A) : a - a = 0 := !add.right_inv
theorem sub_add_cancel (a b : A) : a - b + b = a := !neg_add_cancel_right
theorem add_sub_cancel (a b : A) : a + b - b = a := !add_neg_cancel_right
theorem add_sub_assoc (a b c : A) : a + b - c = a + (b - c) :=
by rewrite [sub_eq_add_neg, add.assoc, -sub_eq_add_neg]
theorem eq_of_sub_eq_zero {a b : A} (H : a - b = 0) : a = b :=
have -a + 0 = -a, by inst_simp,
by inst_simp
theorem eq_iff_sub_eq_zero (a b : A) : a = b ↔ a - b = 0 :=
iff.intro (assume H, eq.subst H !sub_self) (assume H, eq_of_sub_eq_zero H)
theorem zero_sub (a : A) : 0 - a = -a := !zero_add
theorem sub_zero (a : A) : a - 0 = a :=
by simp
theorem sub_ne_zero_of_ne {a b : A} (H : a ≠ b) : a - b ≠ 0 :=
begin
intro Hab,
apply H,
apply eq_of_sub_eq_zero Hab
end
theorem sub_neg_eq_add (a b : A) : a - (-b) = a + b :=
by simp
theorem neg_sub (a b : A) : -(a - b) = b - a :=
neg_eq_of_add_eq_zero (by inst_simp)
theorem add_sub (a b c : A) : a + (b - c) = a + b - c :=
by simp
theorem sub_add_eq_sub_sub_swap (a b c : A) : a - (b + c) = a - c - b :=
by inst_simp
theorem sub_eq_iff_eq_add (a b c : A) : a - b = c ↔ a = c + b :=
iff.intro (assume H, eq_add_of_add_neg_eq H) (assume H, add_neg_eq_of_eq_add H)
theorem eq_sub_iff_add_eq (a b c : A) : a = b - c ↔ a + c = b :=
iff.intro (assume H, add_eq_of_eq_add_neg H) (assume H, eq_add_neg_of_add_eq H)
theorem eq_iff_eq_of_sub_eq_sub {a b c d : A} (H : a - b = c - d) : a = b ↔ c = d :=
calc
a = b ↔ a - b = 0 : eq_iff_sub_eq_zero
... = (c - d = 0) : H
... ↔ c = d : iff.symm (eq_iff_sub_eq_zero c d)
theorem eq_sub_of_add_eq {a b c : A} (H : a + c = b) : a = b - c :=
by simp
theorem sub_eq_of_eq_add {a b c : A} (H : a = c + b) : a - b = c :=
by simp
theorem eq_add_of_sub_eq {a b c : A} (H : a - c = b) : a = b + c :=
by simp
theorem add_eq_of_eq_sub {a b c : A} (H : a = c - b) : a + b = c :=
by simp
theorem left_inverse_sub_add_left (c : A) : function.left_inverse (λ x, x - c) (λ x, x + c) :=
take x, add_sub_cancel x c
theorem left_inverse_add_left_sub (c : A) : function.left_inverse (λ x, x + c) (λ x, x - c) :=
take x, sub_add_cancel x c
theorem left_inverse_add_right_neg_add (c : A) :
function.left_inverse (λ x, c + x) (λ x, - c + x) :=
take x, add_neg_cancel_left c x
theorem left_inverse_neg_add_add_right (c : A) :
function.left_inverse (λ x, - c + x) (λ x, c + x) :=
take x, neg_add_cancel_left c x
end add_group
structure add_comm_group [class] (A : Type) extends add_group A, add_comm_monoid A
section add_comm_group
variable [s : add_comm_group A]
include s
theorem sub_add_eq_sub_sub (a b c : A) : a - (b + c) = a - b - c :=
by simp
theorem neg_add_eq_sub (a b : A) : -a + b = b - a :=
by simp
theorem neg_add (a b : A) : -(a + b) = -a + -b :=
by simp
theorem sub_add_eq_add_sub (a b c : A) : a - b + c = a + c - b :=
by simp
theorem sub_sub (a b c : A) : a - b - c = a - (b + c) :=
by simp
theorem add_sub_add_left_eq_sub (a b c : A) : (c + a) - (c + b) = a - b :=
by simp
theorem eq_sub_of_add_eq' {a b c : A} (H : c + a = b) : a = b - c :=
by simp
theorem sub_eq_of_eq_add' {a b c : A} (H : a = b + c) : a - b = c :=
by simp
theorem eq_add_of_sub_eq' {a b c : A} (H : a - b = c) : a = b + c :=
by simp
theorem add_eq_of_eq_sub' {a b c : A} (H : b = c - a) : a + b = c :=
by simp
theorem sub_sub_self (a b : A) : a - (a - b) = b :=
by simp
theorem add_sub_comm (a b c d : A) : a + b - (c + d) = (a - c) + (b - d) :=
by simp
theorem sub_eq_sub_add_sub (a b c : A) : a - b = c - b + (a - c) :=
by simp
theorem neg_neg_sub_neg (a b : A) : - (-a - -b) = a - b :=
by simp
end add_comm_group
definition group_of_add_group (A : Type) [G : add_group A] : group A :=
⦃group,
mul := has_add.add,
mul_assoc := add.assoc,
one := !has_zero.zero,
one_mul := zero_add,
mul_one := add_zero,
inv := has_neg.neg,
mul_left_inv := add.left_inv⦄
namespace norm_num
reveal add.assoc
definition add1 [has_add A] [has_one A] (a : A) : A := add a one
local attribute add1 bit0 bit1 [reducible]
theorem add_comm_four [add_comm_semigroup A] (a b : A) : a + a + (b + b) = (a + b) + (a + b) :=
by simp
theorem add_comm_middle [add_comm_semigroup A] (a b c : A) : a + b + c = a + c + b :=
by simp
theorem bit0_add_bit0 [add_comm_semigroup A] (a b : A) : bit0 a + bit0 b = bit0 (a + b) :=
by simp
theorem bit0_add_bit0_helper [add_comm_semigroup A] (a b t : A) (H : a + b = t) :
bit0 a + bit0 b = bit0 t :=
by rewrite -H; simp
theorem bit1_add_bit0 [add_comm_semigroup A] [has_one A] (a b : A) :
bit1 a + bit0 b = bit1 (a + b) :=
by simp
theorem bit1_add_bit0_helper [add_comm_semigroup A] [has_one A] (a b t : A)
(H : a + b = t) : bit1 a + bit0 b = bit1 t :=
by rewrite -H; simp
theorem bit0_add_bit1 [add_comm_semigroup A] [has_one A] (a b : A) :
bit0 a + bit1 b = bit1 (a + b) :=
by simp
theorem bit0_add_bit1_helper [add_comm_semigroup A] [has_one A] (a b t : A)
(H : a + b = t) : bit0 a + bit1 b = bit1 t :=
by rewrite -H; simp
theorem bit1_add_bit1 [add_comm_semigroup A] [has_one A] (a b : A) :
bit1 a + bit1 b = bit0 (add1 (a + b)) :=
by simp
theorem bit1_add_bit1_helper [add_comm_semigroup A] [has_one A] (a b t s: A)
(H : (a + b) = t) (H2 : add1 t = s) : bit1 a + bit1 b = bit0 s :=
by inst_simp
theorem bin_add_zero [add_monoid A] (a : A) : a + zero = a :=
by simp
theorem bin_zero_add [add_monoid A] (a : A) : zero + a = a :=
by simp
theorem one_add_bit0 [add_comm_semigroup A] [has_one A] (a : A) : one + bit0 a = bit1 a :=
by simp
theorem bit0_add_one [has_add A] [has_one A] (a : A) : bit0 a + one = bit1 a :=
rfl
theorem bit1_add_one [has_add A] [has_one A] (a : A) : bit1 a + one = add1 (bit1 a) :=
rfl
theorem bit1_add_one_helper [has_add A] [has_one A] (a t : A) (H : add1 (bit1 a) = t) :
bit1 a + one = t :=
by inst_simp
theorem one_add_bit1 [add_comm_semigroup A] [has_one A] (a : A) : one + bit1 a = add1 (bit1 a) :=
by simp
theorem one_add_bit1_helper [add_comm_semigroup A] [has_one A] (a t : A)
(H : add1 (bit1 a) = t) : one + bit1 a = t :=
by inst_simp
theorem add1_bit0 [has_add A] [has_one A] (a : A) : add1 (bit0 a) = bit1 a :=
rfl
theorem add1_bit1 [add_comm_semigroup A] [has_one A] (a : A) :
add1 (bit1 a) = bit0 (add1 a) :=
by simp
theorem add1_bit1_helper [add_comm_semigroup A] [has_one A] (a t : A) (H : add1 a = t) :
add1 (bit1 a) = bit0 t :=
by inst_simp
theorem add1_one [has_add A] [has_one A] : add1 (one : A) = bit0 one :=
rfl
theorem add1_zero [add_monoid A] [has_one A] : add1 (zero : A) = one :=
by simp
theorem one_add_one [has_add A] [has_one A] : (one : A) + one = bit0 one :=
rfl
theorem subst_into_sum [has_add A] (l r tl tr t : A) (prl : l = tl) (prr : r = tr)
(prt : tl + tr = t) : l + r = t :=
by simp
theorem neg_zero_helper [add_group A] (a : A) (H : a = 0) : - a = 0 :=
by simp
end norm_num
attribute [simp]
zero_add add_zero one_mul mul_one
at simplifier.unit
attribute [simp]
neg_neg sub_eq_add_neg
at simplifier.neg
attribute [simp]
add.assoc add.comm add.left_comm
mul.left_comm mul.comm mul.assoc
at simplifier.ac